Developing Informational Text-Based HOTS Assessment Instruments via Google Forms: A Needs Analysis in Indonesian Junior High Schools - Nela Arista; Nurhayati Nurhayati; Ernalida Ernalida (AL-ISHLAH: Jurnal Pendidikan, 2025)
Critical thinking is a key 21st-century skill that remains underdeveloped among junior high school students in Indonesia, as reflected in low literacy and thinking scores. This study responds to the need for valid, practical, and contextual assessments to measure students' higher-order thinking skills (HOTS), particularly in reading informational texts. This research employed a research and development (RD) approach using a modified version of Djiwandono’s development model. The study included needs analysis, instrument design, expert validation, and field testing. Data were collected from 225 seventh-grade students and teachers at SMP Negeri 1 Sekayu using questionnaires, interviews, and instrument trials. The final product—a HOTS assessment instrument—was delivered through Google Forms. The results indicated that both students (97.3%) and teachers (100%) recognized the need for HOTS-oriented questions, especially those using informational texts. The instrument was validated by experts and showed high validity, reliability, appropriate difficulty levels, and effective item discrimination. Additionally, 92.9% of students found Google Forms easy to use and suitable for digital assessment. This study confirms the feasibility and effectiveness of digital HOTS instruments using informational texts. The developed tool supports critical thinking evaluation and aligns with current curricular goals. It also demonstrates the readiness of schools to integrate digital tools for formative assessment.